Alginate Oligosaccharide Alleviated Cisplatin-Induced Kidney Oxidative Stress via Lactobacillus Genus-FAHFAs-Nrf2 Axis in Mice - Zhang, Yubing; Qin, Song; Song, Yipeng; Yuan, Jingyi; Hu, Shanliang; Chen, Min; Li, Lili (Frontiers in Immunology, 2022)
Alginate oligosaccharide is associated with beneficial health effects. Here, we aimed to investigate the mechanism via which alginate oligosaccharides improve kidney oxidative damage and liver inflammation induced by cisplatin chemotherapy via the gut microbiota. C57BL/6J mice treated with cisplatin were administered alginate oligosaccharide via gavage for 3 weeks. Compared to that observed in the cisplatin chemotherapy group without intragastric administration of alginate oligosaccharide, liver inflammation improved in the alginate oligosaccharide group, indicated by reduction in lipopolysaccharide and interleukin-1β (IL-1β) levels. This was accompanied by improvement in the oxidative stress of mice kidneys, indicated by the increase in the levels of superoxide dismutase (SOD), catalase (CAT) and nucleus NF-E2-related factor 2 (Nrf2) in renal tissue, and reduction in the levels of malondialdehyde (MDA) in renal tissue and serum creatinine (Cr) to the levels of the normal control group. Alginate oligosaccharide intervention increased the concentration of fatty acid esters of hydroxy fatty acids (FAHFAs). Alginate oligosaccharide regulated the composition of the intestinal microbial community and promoted Lactobacillus stains, such as Lactobacillus johnsonii and Lactobacillus reuteri. Spearman analysis showed that 5 members of FAHFAs concentrations were positively correlated with Lactobacillus johnsonii and Lactobacillus reuteri abundance. We observed that alginate oligosaccharide increased FAHFAs producing-related bacterial abundance and FAHFAs levels, enhanced the levels of SOD and CAT in kidney tissue, and reduced the levels of MDA via activating Nrf2, thereby ameliorating the renal redox injury caused by cisplatin chemotherapy.